Comparative study of 1D, 2D and 3D ground response analysis of pond ash from odisha under different earthquake motions - Reddy M.V.R.K.; Mohanty S.; Shaik R. (My University, 2025)
It was attempted in the current study to study the one-dimensional (1D), two-dimensional (2D) and three-dimensional (3D) ground response of pond ash collected from Odisha under different earthquake motions. 1D ground response of pond ash deposit was studied by employing equivalent linear and nonlinear analysis methods, viz. SHAKE2000 and Cyclic1D software, respectively. 2D and 3D seismic response analysis of pond ash was investigated by employing Plaxis2D and Plaxis3D, respectively. Response of the pond ash deposit when subjected to Northeast India earthquake (Mw-7.5) and Nepal earthquake (Mw-7.8) was studied here in this study. Results of the response analyses were presented in terms of acceleration, displacement, excess pore pressure and excess pore pressure ratio. It was attempted to perform a comparative study on variation of stated parameters over 1D, 2D and 3D ground response analysis performed in this study. Variation in peak ground acceleration of 1D over 2D and 3D seismic response analysis of pond ash under Northeast India earthquake was 1.21 times and 1.46 times, respectively; whereas under Nepal earthquake was 0.72 times and 0.92 times, respectively. Maximum peak ground displacement was noticed in case of 3D ground response analysis. Pond ash was not susceptible to liquefaction when got excited under both the earthquakes. © Springer Nature Singapore Pte Ltd. 2021.